Sanksi Administratif Malpraktik Bagi Dokter Dan Rumah Sakit Di Indonesia - Miharja, Marjan (DE LEGA LATA: JURNAL ILMU HUKUM, 2020)
This study aimed to examine the forms of sanctions for malpractice committed by doctors and hospitals in the perspective of positive Indonesian law. The method used is the normative legal research method or the library legal research method is the method or method used in legal research conducted by using existing library materials. The results showed malpractice actions carried out by doctors and hospitals have clear legal responsibilities stipulated in Act Number 29 of 2004 concerning Medical Practices. Administratively, all forms of malpractice carried out by doctors and hospitals can be threatened with imprisonment, civil, administrative sanctions, and fines. As for hospitals, they can be sentenced directly and indirectly. In the later, final stages, the final stages of court decisions made by doctors and hospitals can be carried out on license revocation.